Determination of Aflatoxin M1 in Buffalo Milk and Products - Serhat Hepçin; Ali Gücükoğlu (Turkish Journal of Agriculture: Food Science and Technology)
This study aimed to investigate the presence of Aflatoxin M1 (AFM1) in raw buffalo milk and buffalo milk products such as cheese, yogurt, cream, and ice cream by ELISA technique. In the study, 175 samples were investigated, and it was determined that 146 (83.43%) of the samples had AFM1 concentrations below the LOD (limit of detection) value. In 29 samples (16.57%), the AFM1 concentration exceeded the LOD value, and in 7 (4%) of these, the AFM1 concentration was above the legal limits (50 ng/L). While AFM1 was not detected in raw buffalo milk samples, the presence of AFM1 in cheese, yogurt, cream, and ice cream samples was found to be 2.85%, 2.85%, 62.85%, and 14.3%, respectively. 2.85% of cheese samples and 17.1% of cream samples were found contaminated with AFM1 above the allowed legal limits (50 ng/L). As a result, it was determined that the potential for exposure to AFM1 by consuming buffalo cream was higher than the consumption of buffalo milk and other buffalo milk products. However, the detection of AFM1 above legal limits in buffalo milk products poses a serious risk to public health. Therefore, it is extremely necessary for public health to develop effective monitoring programs to control aflatoxin contamination in milk and new strategies to maintain inspections.